Turkish Libraries in the Next Millennium - Doğan Atılgan (Türk Kütüphaneciliği)
This paper examines Turkish Librarianship from the retrospective approach. The manner in which developments in information technology has effected the librarianship, some changes and new responsibilities of the information specialists have been discussed. Although the neccessity for reduction of negative influences information age such as current cultural policy and standarts and reestablishments of law and equilibria in different libraries have been indicated. As a result some suggestions on this subject was dedicated.